Efficacy and safety of tacrolimus compared with ciclosporin-A in renal transplantation: 7-year observational results - Krämer, Bernhard; Krüger, Bernd (Transplant international, 2016)
The European Tacrolimus versus Ciclosporin-A Microemulsion (CsA-ME) Renal Transplantation Study demonstrated that tacrolimus decreased acute rejection rates at 6 months. Primary endpoints of this investigator-initiated, observational 7-year follow-up study were acute rejection rates, patient and graft survival rates, and a composite endpoint (BPAR, graft loss, and patient death). We analyzed data from the original intent-to-treat population (n = 557; 286 tacrolimus, 271 CsA-ME). A total of 237 tacrolimus and 208 CsA-ME patients provided data. At 7 years, Kaplan-Meier estimated rates of patients free from BPAR were 77.1% in the tacrolimus arm and 59.9% in the CsA-ME arm, graft survival rates amounted to 82.6% and 80.6%, and patient survival rates to 89.9% and 88.1%. Estimated combined endpoint-free survival rates were 60.2% in the tacrolimus arm and 47.0% in the CsA-ME arm (P = <0.0001). A higher number of patients from the CsA-ME arm crossed over to tacrolimus during 7 year follow-up: 19.7% vs. 7.9% (P = <0.002). More patients in the tacrolimus group stopped steroids and received immunosuppressive monotherapy. Significantly, more CsA-ME patients received lipid-lowering medication and experienced cosmetic and cardiovascular adverse events. Tacrolimus-treated renal transplant recipients had significantly higher combined endpoint-free survival rates mainly driven by lower acute rejection rates despite less immunosuppressive medication at 7 years.